2021
DOI: 10.3390/cancers13236014
|View full text |Cite
|
Sign up to set email alerts
|

Her2 Expression in Circulating Tumor Cells Is Associated with Poor Outcomes in Patients with Metastatic Castration-Resistant Prostate Cancer

Abstract: HER2-dependent signaling may support the development of metastatic castration-resistant prostate cancer (mCRPC) by activating androgen receptor signaling through ligand-independent mechanisms. From 41 mCRPC patients (including 31 treated with Androgen Receptor Signaling Inhibitors [ARSI]), Circulating Tumor Cells (CTCs) were prospectively enriched with AdnaTest platform and analyzed with a multiplexed assay for HER2 and AR-V7 mRNA expression. Then, we evaluated the impact of HER2 expression on PSA-response, Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some studies have attempted to detect HER2 expression in circulating tumor cells. 39 Based on this, we can reasonably speculate that precision detection and evaluation may become future research hotspots.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have attempted to detect HER2 expression in circulating tumor cells. 39 Based on this, we can reasonably speculate that precision detection and evaluation may become future research hotspots.…”
Section: Discussionmentioning
confidence: 83%
“…After applying all the selection criteria, the final sample comprised 46 articles on metastatic PC [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] ( Supplementary Table S1 ) and 15 articles on localized PC [ 55 , 56 , 57 , 58 , 59 , 60 …”
Section: Resultsmentioning
confidence: 99%
“…They also found that HER2 (ERBB2) was enriched in experimental bone metastases and that dual inhibition of EGFR and HER2 was required for effective bone metastasis treatment [20] . On a related note, Maillet et al fround that HER2 expression by circulating tumor cells in patients with metastatic castration resistant PCa correlated with worse clinical outcome, most importantly overall survival [33] . In testing response of PCa cell lines to trastuzumab (anti-HER2) and cetuximab (anti-EGFR), Andersson et al did not observe additional effects of addition of cetuximab to trastuzumab.…”
Section: Discussionmentioning
confidence: 99%